Values education from the family in the current context - Gudelia Beatriz Brizuela Tornés; Carlos Manuel González Brizuela; Yasel González Brizuela; Delia Luisa Sánchez Pacheco (Centro Provincial de Información de Ciencias Médicas, 2021)
The family possesses an essential function in the training of the future generations, because the foundations for values education reside in it so that they will contribute to the development of the healthy and virtuous society that it is needed. Reason why it is inevitable to improve the theoretical and methodological bases that guide their performance, as well as to achieve effective tools to motivate and train in the display of its educational rector role to build quality generations, which constitutes an indispensable challenge. In this respect, this work is aimed at revitalizing and enriching those principles without obviating the current context that we are living, and some tools are also offered that facilitate a better family performance in the educational work of values.